Increase of Performance and Smoke Emission by Increasing ERG Rate in IDI Diesel Engine using Jatropha Oil and Diesel Fuel Blends - Syaiful MSK Tony Suryo Utomo (Institute of Research and Community Outreach, Petra Christian University, 2013)
Recently, a study of biodiesel fuel use as a substitute of diesel fuel becomes an interesting topic due to critical fossil fuel availability. The use of biodiesel fuel directly into diesel engine without the change of fuel injector parameter causes the problems because of different properties of biodiesel fuel compared with that of diesel fuel. The aim of present study is to investigate experimentally the effect of exhaust gas recirculation (EGR) on the diesel engine performance and smoke emissions by using jatropha oil and diesel fuel blends as the fuel. EGR is one of methods to increase the fuel efficiency of diesel engine. The use of EGR method on diesel engine may also reduce NOx emissions. In this research, EGR temperature is varied to study its effect on the diesel engine consumption and smoke emissions. Jatropha oil blend is in the range of 10 to 30 %. It is found that the high EGR rate expressed the low fuel consumption compared with that of the low EGR rate by using diesel fuel or jatropha oil - diesel fuel blends. The present paper also shows that the high EGR rate results the high smoke emissions for both cases.